2018
DOI: 10.1039/c7py02000g
|View full text |Cite|
|
Sign up to set email alerts
|

A mannose-conjugated multi-layered polymeric nanocarrier system for controlled and targeted release on alveolar macrophages

Abstract: To improve the performance of drug delivery systems in macrophages, targeted ligand-conjugated polymeric carriers have been realized to be vital for targeted, sustainable and controlled drug release with remarkable biocompatibility and bioavailability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Furthermore, the lungs have comparatively low local metabolic activity and, thereby, show no or limited first pass metabolism [ 17 ]. Finally, alveolar macrophages can be targeted for management of pulmonary TB [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the lungs have comparatively low local metabolic activity and, thereby, show no or limited first pass metabolism [ 17 ]. Finally, alveolar macrophages can be targeted for management of pulmonary TB [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated the possibility of using CNTs as a nanocarrier for TB drug delivery and were conducted to overcoming on antibacterial resistance of TB. 15,28 One study in 2019 reported that chitosan-functionalized CNTs could increase the drug permeability of INH in the treatment of TB in the bone and wound tissues. 33 Also, Barros et al, 34 demonstrated the efficacy of naphthoimidazoles together with INH and rifampin, as the main drugs for controlling tuberculosis.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…13 Therefore, the importance of CNTs has been recognized in the pharmaceutical industry. 12,14,15 Multiwall carbon nanotubes (MWCNTs), as drug carriers, should first be functionalized to enhance the biological function. Induction of carboxyl and chlorine on MWCNTs could increase the carrying capacity and reduce the complications symptoms on healthy cells.…”
Section: Introductionmentioning
confidence: 99%
“…Praphakar et al synthesized am annose-conjugated multilayered polymericd rug-delivery system based on chitosan and sodium alginatec omprising two anti-TB chemotherapeutics, rifampicin(RF) and isoniazid (INH). [87] Thismannose-coated delivery system allows the efficient macrophage-targeting delivery, the combination of multiple anti-TB agents with enhanced oral bioavailability,a nd drug release in as ustained manner.S imilarly,S arwar et al and Chaubeye tal. both developed anti-VL-reagent-loaded mannosylated nanocarriersf or receptor-mediated macrophage targeting with bettert herapeutic indexes.…”
Section: Mannose-based Nanomaterials In Other Applicationsmentioning
confidence: 99%
“…Praphakar et al. synthesized a mannose‐conjugated multilayered polymeric drug‐delivery system based on chitosan and sodium alginate comprising two anti‐TB chemotherapeutics, rifampicin (RF) and isoniazid (INH) . This mannose‐coated delivery system allows the efficient macrophage‐targeting delivery, the combination of multiple anti‐TB agents with enhanced oral bioavailability, and drug release in a sustained manner.…”
Section: Mannose‐based Nanomaterials In Biomedical Applicationsmentioning
confidence: 99%